2022
DOI: 10.1111/jog.15445
|View full text |Cite
|
Sign up to set email alerts
|

The association between caffeine exposure during pregnancy and risk of gestational hypertension/preeclampsia: A meta‐analysis and systematical review

Abstract: The potential effect of caffeine exposure during pregnancy on gestational hypertension (GH)/preeclampsia has attracted attention but remains unclear. A systematic literature search of PubMed, Embase and Cochrane Library databases was performed until March 2022. Observational studies assessing the association between caffeine exposure during pregnancy and the risk of GH/preeclampsia were included. The study protocol was registered in PROSPERO: CRD42022322387. Ten studies involving 114984 pregnant women (2548 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The caffeine content of black tea is higher than that of oolong and green tea [ 33 ]. Still, a recent meta-analysis of ten studies involving 114,984 pregnant women indicated no association between caffeine exposure during pregnancy and the risk of gestational hypertension or pre-eclampsia [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The caffeine content of black tea is higher than that of oolong and green tea [ 33 ]. Still, a recent meta-analysis of ten studies involving 114,984 pregnant women indicated no association between caffeine exposure during pregnancy and the risk of gestational hypertension or pre-eclampsia [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with other studies which have shown that caffeine intake was not associated with increased risk of PE or sPTB. 35 , 36 A possible protective effect was observed as those with moderate paraxanthine levels throughout pregnancy had a lower risk of GDM compared with those with low levels. Whereas it is difficult to separate the effects of diet, body mass index and caffeine intake on this risk given that caffeine is found in a wide array of foods and drinks, the potential benefit of caffeine consumption in reducing the risk of GDM has been reported previously.…”
Section: Discussionmentioning
confidence: 99%